Hydrogen Sulfide Alleviates Skeletal Muscle Fibrosis via Attenuating Inflammation and Oxidative Stress - Zhao, Linlin; Liu, Xiaoguang; Zhang, Jing; Dong, Gaoyang; Xiao, Weihua; Xu, Xin (Frontiers in Physiology, 2020)
The purpose of this study was to investigate the effect of exogenous hydrogen sulfide (H2S) treatment on skeletal muscle contusion. We established a skeletal muscle contusion model (S group) and an H2S treated of skeletal muscle contusion model (H2S group). Gastrocnemius muscles (GMs) were collected at day1, day5, day10 and day15 after injury, and comprehensive morphological and genetic analyses was conducted. H2S treatment reduced M1 macrophage (CD68), pro-inflammatory cytokines (TNF-α, IFN-γ, IL-1β, and IL-6), chemokines (CCL2, CCR2, CCL3, CCL5, CXCL12, and CXCR4), matrix metalloproteinases (MMP-1, MMP-2, MMP-9, and MMP-14) and oxidative stress factor (gp91phox) expression levels, improved M2 macrophage (CD206) level. Thus, exogenous H2S treatment reduced inflammation and oxidative stress, attenuated skeletal muscle fibrosis, and partly improved skeletal muscle injury.